Pengaruh Work Family Conflict dan Disiplin Kerja Terhadap Turnover pada RSIA Eria Bunda Pekanbaru - Sehani Sehani; Jannatul Firdaus (Al-Manar Journal of Economic and Social Studies, 2025)
In relation to achieving organizational goals, every superior is required to always be careful in making decisions and paying attention to employees, especially in dealing with work family conflict and work discipline of nurses so that good performance and a decrease in turnover rates are created. The purpose of this study was to determine the effect of work family conflict and work discipline partially and simultaneously on nurse turnover. This study was conducted at Eria Bunda Hospital located at Jl. Ahmad Dahlan Number 163, Kampung Tengah, Sukajadi District, Pekanbaru City, Riau. The population in this study was 76 nurses, and the sample was 76 people using the census method or saturated sample. The results of the study explained that partially and simultaneously the variables of work family conflict and work discipline had a significant effect on the turnover variable in nurses at Eria Bunda Hospital Pekanbaru, with an R Square value of 0.734 explaining that work family conflict and work discipline can affect turnover in nurses at Eria Bunda Hospital Pekanbaru by 73.4% while the remaining 26.6% was influenced by other variables not examined in this study.